2012
DOI: 10.1111/j.1365-3024.2012.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Th17/Treg imbalance in patients with liver cystic echinococcosis

Abstract: Summary Echinococcosis is a chronic parasitic infectious disease regulated by T‐cell subsets. CD4+ CD25+ FoxP3 +  regulatory T (Treg) cells and Th17 cells have been described as two distinct subsets and have the opposite effect on inflammation. Th17/Treg balance controls inflammation and may play an important role in the pathogenesis of immune evasion. To assess whether this balance was broken, we detected Th17/Treg functions in different levels including cell frequencies, related cytokines secretion and key t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
4
39
0
Order By: Relevance
“…Moreover, PSC present Fc-binding activity (Baz et al 1998) and express immune regulatory antigen B and EgTeg (Ortona et al 2005;Sanchez et al 1991;Monteiro et al 2010). Recently, T-regulatory and myeloid-derived suppressor cells have been found to be systemically expanded in mice with E. granulosus infection and in CE patients (Pan et al 2013;Tuxun et al 2012). Taken together, these results support the presence of an immunomodulatory environment downregulating both Th1 and Th2 responses and favoring parasite survival.…”
Section: Immune Response To E Granulosussupporting
confidence: 54%
“…Moreover, PSC present Fc-binding activity (Baz et al 1998) and express immune regulatory antigen B and EgTeg (Ortona et al 2005;Sanchez et al 1991;Monteiro et al 2010). Recently, T-regulatory and myeloid-derived suppressor cells have been found to be systemically expanded in mice with E. granulosus infection and in CE patients (Pan et al 2013;Tuxun et al 2012). Taken together, these results support the presence of an immunomodulatory environment downregulating both Th1 and Th2 responses and favoring parasite survival.…”
Section: Immune Response To E Granulosussupporting
confidence: 54%
“…It has been reported that several Th subsets, such as Th1/Th2 cells [57] and Th17/Treg cells [19], are involved in the regulating the immune response of Echinococcosis. Th1 and Th2 cells mainly exert their biological effects through secreting the cytokines of IFN- γ and IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that the levels of peripheral Th17 cells and IL-17 were slightly lower in the CE patients than in health control, suggesting there was imbalance between Th17 cells and Treg cells in CE patients [19]. Therefore, the purposes of this study are as follows: (i) to explore the change of Th9 cells in the CE patients before and after treatments; (ii) to study the characteristics of the changes of Th9-related cytokines and transcription factors; (iii) to study the correlations between Th9 and Th1, Th2, Treg, and Th17 cells in CE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Afflicted patients exhibit higher levels of regulatory T-cells, IL-10 and TGF-␤ in vivo (Chandrasekhar and Parija, 2009;Tuxun et al, 2012). It was also shown that antigen B of Echinococcus granulosus impairs maturation of dendritic cells leading to impaired responses to inflammatory stimuli and induces a Th2-dominated immune response (Rigano et al, 1995).…”
Section: Concise Immune-pathology Of Cystic Echinococcosis (Ce)mentioning
confidence: 96%